High-efficiency terahertz devices based on cross-polarization converter. Issue 1 (December 2017) - Zhao, Huan; Wang, Xinke; He, Jingwen; Guo, Jinying; Ye, Jiasheng; Kan, Qiang; Zhang, Yan
Abstract Metasurface-based devices have been investigated intensively because of their attractive properties but these devices generally suffer from low efficiency. Here we demonstrate several high-efficiency terahertz (THz) devices based on cross-polarization converters that is composed of bilayer metasurface-based structures. The converter can transfer the polarization states of transmitted THz waves from thex -direction into they -direction with an experimental conversion efficiency of 85%. This high-efficiency transfer mechanism is investigated in detail. Furthermore, this kind of devices can be fabricated easily. A THz metalens is designed and fabricated and its focusing and imaging properties are investigated experimentally. A pure phase THz hologram that can generate different images on different propagation planes is also designed and the image reconstruction capabilities of the phase holograms are demonstrated experimentally. The performance levels of all designed devices show excellent agreement between the theoretical expectations and the corresponding experimental results. This technology may pave the way towards practical applications of such metasurface devices.